Topical issues of modern urology : educational manual - Dovbysh, M. A.; Dovbysh, I. M.; Mishchenko, O. M.; Довбиш, Михайло Афанасійович; Довбиш, Ігор Михайлович; Міщенко, Олена Михайлівна (Запорізький державний медико-фармацевтичний університет, 2023)
The study guide contains a list of knowledge and practical skills that must be mastered by foreign students of the IV year of the international faculty in the discipline "Urology".